HUBUNGAN USIA DAN JENIS KELAMIN DENGAN KEJADIAN STROKE DI RSUD KHZ MUSTHAFA TASIKMALAYA 2023 - nurul, nasyifa (PERDOSNI, 2025)
ABSTRACT Introduction: According to the 2018 Riskesdas data, the prevalence of stroke in Indonesia indicates a potential global increase in the coming years as the population ages. Based on gender characteristics, the prevalence of stroke in males is 8.8%, and in females, it is 7.9%, showing only a slight difference, with males being slightly more susceptible to stroke. Aim: To determine the relationship between age and gender characteristics with the incidence of stroke at KHZ Musthafa General Hospital, Tasikmalaya, in 2023. Method: This study uses a retrospective observational design. Data were obtained through secondary data in the form of medical records of patients who were hospitalized at KHZ Musthafa General Hospital in 2023. The sample was taken using total sampling. Data were tested using the chi-square test. Results: The highest number of ischemic and hemorrhagic stroke patients was found in the 45-64 age group. Hemorrhagic stroke occurred more frequently in females, while the incidence of ischemic stroke was similar between males and females. Discussion: There is a very significant relationship between age and the incidence of both hemorrhagic and ischemic stroke. Individuals over the age of 45 have a 12-fold higher risk of hemorrhagic stroke and a 24-fold higher risk of ischemic stroke compared to those under 45. Gender does not have a significant relationship with the incidence of hemorrhagic stroke, while for ischemic stroke, females show a lower risk compared to males. Keywords: Age, Gender, Stroke